The berenstain bears get the gimmies ebook - Berenstain, Stan (First Time Books: Berenstain Bears., 2010)
Come for a visit in Bear Country with this classic First Time Book® from Stan and Jan Berenstain. Brother and Sister are having a bad case of the “gimmies.” Whenever they don’t get what they want, they throw a tantrum. But is this really the best way to handle their emotions? This beloved story is a perfect way to teach children about self-control and the importance of compromise.